SOCIODEMOGRAPHIC FACTORS ASSOCIATED WITH THE USE OF RIVERINE LATRINES: A CASE STUDY IN SUNGAI RAYA VILLAGE, SEPAUK DISTRICT - Elvi Juliansyah; Sunarti, Sunarti; Rika Yuanita Pratama; Ria Damayanti (Prosiding Seminar Nasional Indonesia, 2025)
Background: Open defecation remains a major challenge in sanitation development in rural Indonesia, including West Kalimantan. Riverine latrines are one of the means still used by the community, influenced by various sociodemographic factors. Objective: To examine the relationship between gender, age, education, and family income with the use of river latrines in Sungai Raya Village, Sepauk District. Methods: This was a quantitative study with a cross-sectional approach involving 278 respondents. Data were collected through questionnaires and analysed using odds ratio and chi-square tests. Results: The use of river latrines is still high (65.8%). There was no significant association between gender (p=0.219) and education (p=0.981) with river latrine use. However, there was a significant association between age (p=0.016; OR=1.994) and income (p=0.023; OR=1.928) with the practice. Respondents aged ≤31 years and earning ≤ MSE were more likely to use river latrines than other groups. Conclusion: Age and family income significantly contributed to the use of river latrines, while gender and education did not. Community-based sanitation program interventions need to consider economic factors and the younger generation as agents of sanitation behaviour change.